Unravelling healthcare access disparities in stroke care: a comprehensive analysis of socio-economic and racial disparities impacting patient outcomes - Roxas, Eryka Thelline; Narra, Sushmitha Priya; Martis, Nigel Leon; Afthab, Rasha Konane; Nanavati, Anvit; Chodisetti, Naga Siva Naveen (International Journal of Research in Medical Sciences, 2026)
Background: Stroke is a primary cause of chronic disability in the United States (U. S.). The annual prevalence in 2022 is 84-262 per 100,000 people, with a 102% increase since 2021. This has led to a reduced quality of life index and increased depression rates, especially in the elderly population. Thus, the primary aim of our study was to determine any healthcare access disparities due to various socioeconomic and demographic factors, and the type of insurance companies used. Methods: A retrospective observational study was conducted using the BRFSS (behavioral risk factor surveillance system) 2021 data. Descriptive and logistic regression analyses using the web enabled analysis tool (WEAT) were performed to assess various socioeconomic factors, demographic factors, and the type of insurance plans used. Results: A total of 341,299 people were analyzed based on demographic and socioeconomic factors, and 403,145 people were analyzed based on access to healthcare and health status. Patients aged ≥65 years had the highest risk of developing stroke (4.97; p<0.0001). Individuals who were unable to work had the highest risk of stroke development (5.13; p<0.0001). Participants earning more than 200,000 had the lowest risk of stroke development (0.49; p<0.0001). Hispanic participants had the lowest risk of stroke (0.75; p<0.0016). Participants with Medicare insurance were most likely to develop stroke (4.77; p<0.0001). Conclusions: Healthcare access disparities were noted based on various socioeconomic and demographic factors. Identifying these factors is important to minimize disparities, along with increasing affordability and accessibility to various stroke services, aiding in reducing its incidence.